Classi cation of magnetic configurations using machine learning algorithms - Bokul, Saffat; Abdus Shukur, Samiha Sabrin Md; Ahmed, Saquib (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.